Is It Really the Result of a Concussion? Lessons From a Case Study - McGeown, J; Hume, P; Kara, S; Neary, P; Gardner, W (Springer (part of Springer Nature), 2019)
Background Within the last two decades, attitudes have shifted from considering sports-related concussion as an insignificant minor injury with no long-term repercussions to a potentially serious brain injury garnering attention from media, clinicians, researchers, and the general public. Objectives To conduct a case study to determine the underlying cause of persistent issues suspected to be associated with a history of sports-related concussion. Protocol Participant A underwent neurophysiological testing following the Neary protocol (assessment of cerebrovascular and cardiovascular variables), comprehensive concussion assessment at a dedicated sports concussion clinic (history, neurological assessment, cervical spine screening, vestibulo-ocular screening, SCAT-5, and exercise testing), referral to a neurologist, structural MRI scan, and referral for specialised assessment at a dedicated dizziness and balance centre. Results Despite a history of multiple sports-related concussions, Participant A’s persistent symptom reports were associated with peripheral vestibular dysfunction and otolithic dysfunction seemingly unrelated to his concussion history. Discussion Lessons from Participant A’s case study showed that on-going symptoms that patients may associate with the effects of concussions may instead be due to unrelated causes that share similar symptomology. Conclusion This research exemplifies the importance of a multi-disciplinary assessment using a repeated testing protocol.
Keywords: Sports medicine; Concussion; Vestibular; Assessment; Persistent symptoms